Current surgical techniques for the management of pediatric glaucoma: A literature review - Aktas, Zeynep; Gulpinar Ikiz, Gokcen Deniz (Frontiers in Ophthalmology, 2023)
Pediatric glaucoma surgery is challenging due to its diverse and complex pathophysiology, altered anterior segment anatomy, greater potential for failure, and complications compared to adult patients. Moreover, numerous challenges are associated with long-term postoperative management. Thus, when dealing with childhood glaucoma, it is important to consider potential complications in addition to the benefits of each intervention. The purpose of this article is to review recently published literature to shed light on the most recent surgical techniques for the safe and effective treatment of childhood glaucoma. Current literature shows that goniotomy and trabeculotomy are the first choices for the management of primary congenital glaucoma. Although older children with phakic eyes seem to benefit from trabeculectomy with adjunctive mitomycin C, it carries a long-term risk of bleb-related endophthalmitis. Glaucoma drainage devices may be preferred for patients with secondary or refractory glaucoma. However, hypotony or tube-related complications are common and encountered more often in children than in adults. Cyclodestructive procedures are also an option for cases in which filtering surgery has failed, but they can also be used as a temporizing measure to reduce the rate of complications in high-risk patients. However, their outcomes can be unpredictable, in terms of efficiency and complications. Finally, minimally invasive glaucoma surgery (MIGS) as the sole alternative treatment or as an adjunctive surgical procedure is a relatively new path for pediatric patients.